Figurative Language in Translation: A Study of J.P. Clark’s The Ozidi Saga - Teilanyo, Diri (Meta, 2007)
AbstractThe interlingual translation of figurative expressions and idioms is a particularly sensitive task, especially in literary texts where the figurativeness of the language is an inalienable part of the text as a literary piece. Since modern thinking on translation favours fidelity to the source text, the translator is required to maintain – rather than improve, reduce or otherwise alter – the figurative texture of the source text in the target text. In this paper, we investigate the felicity of J.P. Clark’s Izon-English translation in his The Ozidi Saga. We point out that felicitous as Clark’s translation is in general, there are noticeable cases of improvement, impoverishment and alteration, alongside full equivalence, in the figurative texture of the translation when viewed against the Izon text by a sensitive Izon- English bilingual. From this we argue that any form of alteration is a literary disservice to the source text, the source culture and the target audience. We propose that the literary translator should do his utmost to retain the figurative level of the source-text language in the target text, even if this involves literalism and some other violation of the basic code of the target language while annotations and glossaries may be freely employed.